Precipitation of binary quasicrystals along dislocations - Zhiqing Yang (Nature Portfolio, 2018)
Quasicrystal precipitation in alloys should be favored at dislocations, which break crystal symmetry, but almost all precipitates at dislocations are periodic. Here, the authors show rare quasicrystal formation along dislocations in a magnesium zinc alloy with atomic resolution.